If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(8p + 6) + -2(6 + -17p) = 3(2 + 3p) Reorder the terms: -3(6 + 8p) + -2(6 + -17p) = 3(2 + 3p) (6 * -3 + 8p * -3) + -2(6 + -17p) = 3(2 + 3p) (-18 + -24p) + -2(6 + -17p) = 3(2 + 3p) -18 + -24p + (6 * -2 + -17p * -2) = 3(2 + 3p) -18 + -24p + (-12 + 34p) = 3(2 + 3p) Reorder the terms: -18 + -12 + -24p + 34p = 3(2 + 3p) Combine like terms: -18 + -12 = -30 -30 + -24p + 34p = 3(2 + 3p) Combine like terms: -24p + 34p = 10p -30 + 10p = 3(2 + 3p) -30 + 10p = (2 * 3 + 3p * 3) -30 + 10p = (6 + 9p) Solving -30 + 10p = 6 + 9p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-9p' to each side of the equation. -30 + 10p + -9p = 6 + 9p + -9p Combine like terms: 10p + -9p = 1p -30 + 1p = 6 + 9p + -9p Combine like terms: 9p + -9p = 0 -30 + 1p = 6 + 0 -30 + 1p = 6 Add '30' to each side of the equation. -30 + 30 + 1p = 6 + 30 Combine like terms: -30 + 30 = 0 0 + 1p = 6 + 30 1p = 6 + 30 Combine like terms: 6 + 30 = 36 1p = 36 Divide each side by '1'. p = 36 Simplifying p = 36
| 3x^2+7x+30=0 | | -0.9x+8.19=-0.7x+4.79 | | (3/11)z=-5 | | lnx-2ln=ln^4 | | 4(m-3)=8m-40 | | 10=x+5-2x | | y-10=37 | | 14y^2=18 | | 7y+9+3y+9=143 | | a+17=-19 | | -4.5a=-32.4 | | -(5/9)k=2 | | x+56=x-23 | | 7x+9=4x+12 | | a+19=-17 | | (10t-5t+14)+(11t-8)= | | 5y+14-8y=-20 | | 7w-4w-3=12 | | 0.7x-0.3x+5=7 | | 3x=450 | | 84=20x | | 3x+4x-8=2(2x+5) | | 2x=8x+2 | | 3y^2-16y+20=0 | | -12=-6x+2(x-4) | | -9z=9 | | 3.2=1.4+x | | 3x-8=2x+17 | | -v+2v+6=-3 | | 24x+18y= | | 3y+12=2y | | 2x^2-8x+2y^2+20y=12 |